A comprehensive review on the impact of cervical spondylosis on quality of life and its management through Unani system of medicine: a review - Fasihuddeen; Habib, Abdul; Aziz, Abdul; Ahmad, Belal; Danish, Mohammad (International Journal of Research in Medical Sciences, 2025)
In the Unani system of medicine, cervical spondylosis is categorized under the broad term known as Waja-ul-Mafasil, which encompasses a wide range of joint disorders including inflammatory, non-inflammatory, infectious, metabolic, and other musculoskeletal ailments. Cervical spondylosis specifically refers to the degenerative changes in the intervertebral discs and adjacent vertebrae in the cervical spine, primarily caused by age related wear and tear. Given the limitations and side effects associated with long term conventional treatments and the considerable impact of the condition on an individual’s physical, mental, and social wellbeing many patients explore alternative therapies. Unani medicine offers various treatment strategies, known as Tadabeer, for managing joint related conditions. This literature review aims to evaluate the existing evidence provided by classical Unani scholars and assess clinical studies on the effectiveness of different regimenal therapies in alleviating joint pain through Unani approaches. The review was conducted using databases such as Google Scholar, PubMed, Science Direct, and Medline, along with classical Unani manuscripts accessed from the library of State Unani Medical College, Prayagraj, Uttar Pradesh, India. Considering the inadequacy of conventional medical treatments, Unani medicine presents a promising alternative through its comprehensive methods including dietary regulations, regimenal procedures, and pharmacological interventions for managing cervical spondylosis.